Margaret Atwood’s The Handmaid’s Tale as a Dystopian Novel - Gogoi, Daisy Priya (International Journal of Psychosocial Rehabilitation, 2020)
The dystopian world is a nightmare for anyone who lives through it or encounters experiences related to such a society. There is no individual freedom, right to privacy, freedom of speech or even thought. People become pawns in the hands of an autocratic system which rules the lives of the people. Any voice raised against such a society is silenced by brutal violence or death. The system rules not only through political power, but ideologies as well. They condition the people through educational institutions and Churches in the attempt to make the tyranny seem natural. Women suffer the worst. They have no right over their bodies or their children. Indeed, the people are kept so terrified and vulnerable that they never rebel against the injustices committed against them by the government in power. Such a horrific and hopeless society is presented by Margaret Atwood in her novel The Handmaid’s Tale. The tale narrates the tale of Offred, who is forced to leave her family and work as, in every sense, as a sex slave. She, like the other handmaids, are treated as mere baby producing machines and have no right over their privacy. Through the character of Offred, Atwood reveals the dangers of exploiting one’s own rights, thinking they are for granted and warns her readers of a world of dystopia. My paper, in this respect, aims to explore the themes used by Atwood in The Handmaid’s Tale to elevate it to the level of dystopia. It also analyzes the various episodes and instances of dystopia presented in the novel.